Penerapan Sistem Resi Gudang Atas Komoditas Hasil Pertanian Di Kabupaten Cilacap - Hapsari, Indri; Sarono, Agus (Notarius, 2023)
AbstractWarehouse receipt is a certificate of ownership of collateral that is specifically registered and issued by the warehouse manager with the approval of the supervisory agency. The purpose of writing a journal is to find out the application of the warehouse receipt system for agricultural commodities in Cilacap and the role the Cilacap Regency local government in implementing the warehouse receipt system for agricultural commodities. The research method used is empirical juridical research method. The results is issueance of the Warehouse Receipt system in Cilacap starting when the request is made by the owner of the goods individually and collectively. The implementation of the warehouse receipt in the Cilacap Regency has not been running well due to the lack of socialization of warehouse receipts from the Cilacap Regency Government and the insufficient budget from the central government or local government. The conclusion is the implementation of the warehouse receipt for agricultural commodities in the Cilacap Regency which has only been running for a year has noot been running effectively with regulated number 9 of 2011 and there is a lack of socialization from the local government of Cilacap Regency in implementing warehouse receipts to farmers.Keyword: warehouse receipt; local government; agriculture.AbstrakResi gudang merupakan surat kepemilikan atas barang jaminan yang terdaftar secara khusus dan dikeluarkan pengelola gudang dengan persetujuan dari badan pengawas. Tujuan penulisan jurnal penelitian yaitu untuk mengetahui penerapan sistem resi gudang atas komoditas hasil pertanian di Cilacap dan peran dari pemerintah daerah Kabupaten Cilacap dalam penerapan sistem resi gudang komoditas pertanian. Metode penelitian yang digunakan dalam penulisan jurnal ini adalah metode penelitian yuridis empiris. Hasil penelitian dari pembahasan jurnal ini yaitu penerbitan Sistem Resi Gudang di Kabupaten Cilacap dimulai saat permohonan oleh pemilik barang secara individu kolektif. Pelaksanaan sistem resi gudang di Kabupaten Cilacap yang belum berjalan dengan baik dikarenakan kurangnya sosialisasi mengenai resi gudang dari Pemerintah Kabupaten Cilacap dan belum tercukupinya anggaran dari pemerintah pusat ataupun pemerintah daerah. Simpulan dari penelitian ini adalah penerapan sistem resi gudang atas komoditas pertanian di Kabupaten Cilacap yang baru berjalan setahun belum berjalan dengan efektif sesuai dengan UU No. 9 Tahun 2011 dan terdapat kendala kurangnya sosialisasi dari pemerintah daerah Kabupaten Cilacap dalam melaksanakan resi gudang kepada petani.Kata kunci: resi gudang; pemerintah daerah; pertanian.